Analisis Quality Service Layout Terhadap Humanistik Effect (study kasus pada Rumah Sakit Umum Nusalima Pekanbaru) - Paulus Ananto Nainggolan; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to analysis the effect caused by variable Qulity Service Layout consisting of Ambient Condition (with respect to environmental conditions). Spatial Layout and Functional (spacious layout and function) and signs / symbols and Artefact (signs / symbols and artifacts). The population of this study amounted to 31 548, while the return of the sample using accidental sampling technique in order to obtain a sample of 100 people. The method of analysis used in this research is descriptive quantitative method, simultaneous analysis and partial. The results show that the Partial Simultaneous and Ambient Condition, Functional and Spatial Layout and sign / symbol and artefact effect on Humanistic Effect on General Hospital Nusalima Pekanbaru, and ambient condition has the most dominant influence on the humanistic effect on General Hospital Nusalima Pekanbaru.Keywords : Quality Service Layout. Ambient Condition, Spacial Layout And Fungsional, Sign/symbols And Artefact, Humanistik Effect.